DISIPLIN PASAR DAN PENGATURAN PERBANKAN: KOMPLEMEN ATAU SUBSTITUSI? - Muazaroh Muazaroh (Jurnal Ekonomi dan Bisnis, 2009)
The banking crises over the last two decades around the world has renewed the interestin market discipline in banking systems. This interest is not merely academic, but it alsoapparent in recent policy initiatives such as the latest capital proposal by The Basel Commiteeon Banking Supervision. The new Basel Capital Accord has 3 pillars. Pillar 3 is disclosurerequirement to enhance market discipline. Market discipline has the potential to reinforcepillar 1 ( minimum capital standar) and pillar 2 (supervisory review process) and promote safetyand soundness in banks and financial systems. The first objective of this paper is to explainbank regulatory and the important of market discipline to complement bank regulatory. Thesecond objective is to explain the framework of market discipline theory and ask some issue:what is market discipline, why the call for market discipline, how market discipline relates toagency conflict in finance theory and how is the framework of market discipline in banking.The third objective is to review some empirical research in market discipline.Keywords : Banking Crises, Moral Hazard, Market Discipline and Bank Regulatory